Exposure to household air pollution from biomass cookstoves and self-reported symptoms among women in rural Honduras. Issue 2 (3rd March 2020) - Walker, Ethan S.; Clark, Maggie L.; Young, Bonnie N.; Rajkumar, Sarah; Benka-Coker, Megan L.; Bachand, Annette M.; Brook, Robert D.; Nelson, Tracy L.; Volckens, John; Reynolds, Stephen J.; L'Orange, Christian; Africano, Sebastian; et al.
ABSTRACT: Household air pollution from combustion of solid fuels is an important risk factor for morbidity and mortality, causing an estimated 2.6 million premature deaths globally in 2016. Self-reported health symptoms are a meaningful measure of quality of life, however, few studies have evaluated symptoms and quantitative measures of exposure to household air pollution. We assessed the cross-sectional association of self-reported symptoms and exposures to household air pollution among women in rural Honduras using stove type (traditional [n = 76]; cleaner-burning Justa [n = 74]) and 24-hour average personal and kitchen fine particulate matter (PM2.5 ) concentrations. The odds of prevalent symptoms were higher among women using traditional stoves vs Justa stoves (e.g. headache: odds ratio = 2.23; 95% confidence interval = 1.13–4.39). Associations between symptoms and measured PM2.5 were generally consistent with the null. These results add to the evidence suggesting reduced exposures and better health-related quality of life among women using cleaner-burning biomass stoves.